2022
DOI: 10.1111/jac.12584
|View full text |Cite
|
Sign up to set email alerts
|

Physiological traits for evaluating heat‐tolerance of Australian spring wheat cultivars at elevated CO2

Abstract: High temperatures and increasing CO2 concentrations are a major threat to global wheat (Triticum aestivum L.) production, demanding the development of heat‐tolerant wheat cultivars. Plant physiological traits are potential surrogates for evaluating genetic variation for crop stress tolerance. This research evaluated 23 Australian wheat cultivars and two breeding lines for heat‐tolerance by characterising the associated physiological traits. The interactive effects of heat‐stress and elevated CO2 were studied u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 84 publications
1
3
0
Order By: Relevance
“…These ndings also agrees with the ndings of (Berry and Bjorkman, 1980) who reported that transpiration is temperature dependent. This behavior is also in agreement with (Ullah et al, 2020;Bokshi et al, 2022), who observed an increase in transpiration rate under HS in tomato genotypes. Overall, S. chacoense recorded a decrease in transpiration rate, which shows the intraspecies differences between genotypes in transpiration may be due to their differences in morphology.…”
Section: Discussionsupporting
confidence: 92%
“…These ndings also agrees with the ndings of (Berry and Bjorkman, 1980) who reported that transpiration is temperature dependent. This behavior is also in agreement with (Ullah et al, 2020;Bokshi et al, 2022), who observed an increase in transpiration rate under HS in tomato genotypes. Overall, S. chacoense recorded a decrease in transpiration rate, which shows the intraspecies differences between genotypes in transpiration may be due to their differences in morphology.…”
Section: Discussionsupporting
confidence: 92%
“…According to the results of their works on faba bean (Vicia faba L.), Bishop, Potts [43] reported some explanation of the reduction of yield as a result of the long exposure of the plants to the heat stress. They stated that flowers were the most affected part of the plant under heat stress conditions, due to reduced pollen viability and germinability in many crop plants [44][45][46][47][48][49]. Many researchers demonstrated that although the male and female reproductive organs of the common bean were the most sensitive to heat stress, the male organs suffered more damage [20,50].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the transpiration water of the crops was sufficient in W2 due to the irrigation during the flowering stage, and thus canopy temperature differences among varieties were small [75,84]. Recent studies also highlighted that no significant or weak correlation between canopy temperature and physiological traits, e.g., leaf chlorophyll content, LAI and Pn, under normal or mild water stress [85][86][87]. In this study, these results suggest that canopy temperature alone could not reflect the physiological changes of crops well under mild water stress.…”
Section: Ct-uav In Relation To Ground-based Physiological Traits In D...mentioning
confidence: 99%